Interlegality Perkawinan Beda Agama Vis a Vis Surat Edaran Mahkamah Agung Nomot 2 Tahun 2023 tentang Penolakan Permohonan Pencatatan Perkawinan Beda Agama di Indonesia - Noer Yasin; Musataklima Musataklima; Ahmad Wahidi (Law Policy Strategy Agency, Ministry of Law of The Republic of Indonesia, 2023)
The polemic of interfaith marriages is not a new problem at the legal level in Indonesia, especially with the issuance of Supreme Court Circular Letter (SEMA) Number 2 of 2023 for District Courts to reject requests for registration of interfaith marriages. This has caused pros and cons in the community. The purpose of this research is to elaborate on the impact on the independence of judges and the constitutional rights of marriage actors, as well as the position of SEMA when faced with the rights of interfaith marriages conducted abroad and brought to Indonesia. This research can enrich insights into the discourse of interfaith marriage in Indonesia. This research uses a normative legal research method that relies on primary, secondary, and tertiary legal materials analyzed prescriptively. The results of this study are, First, SEMA can interfere with the independence of judicial power itself, where the Supreme Court is one of the actor of SEMA. Secondly, SEMA impacts the non-fulfillment of the constitutional rights of actors of interfaith marriages to obtain legal certainty, equality before the law, and legal protection. Thirdly, SEMA can trigger smuggling of law in interfaith marriages where the legal consequences must be recognized based on the principles of rights derived from foreign law, the principle of reciprocity, and the principle of comitas gentium. These three principles underlie the inter legality of interfaith marriages, so they have transnational legality. This research recommends that the Supreme Court revoke the SEMA that has been issued.